The Transformation of New Men in Realizing a Sakinah Family and Its Implications for Family Law Reform in Indonesia - Hadjar, Nurmalina (Universitas Islam Negeri Raden Intan Lampung, 2025)
This research examines the transformation of new men in realizing a sakinah family. The new men's alliance has recently shown the existence of the struggle for gender justice, against patriarchal culture. This new male transformation places women as equal partners, supporting each other and taking roles in family life so that they can realize a sakinah family. This research is a field research or filed research, conducting interviews with new male alliances in Indonesia, analyzed qualitatively using the theory of mubadalah. The findings of this study are that the new men's alliance is a form of male community that has the awareness that women are a subject that is equal to men. The formation of a sakinah family, new men argue that a sakinah family can be achieved by cooperating with mubadalah between husband and wife. New men realize that in the family is a shared responsibility. Regulations in Indonesia as in the Marriage Law and KHI provide rules that women are only responsible as housewives, with the struggle of the new male alliance providing recommendations that in this modern era the need for regulatory changes that accommodate the equal role of husbands and wives in the formation of a sakinah family.Keywords: Transformation, New Men's Alliance, Sakinah Family